Effectiveness of an app-based intervention for unintentional injury among caregivers of preschoolers: protocol for a cluster randomized controlled trial - Peishan Ning; Bo Chen; Peixia Cheng; Yang Yang; David C. Schwebel; Renhe Yu; Jing Deng; Shukun Li; Guoqing Hu (BMC, 2018)
Abstract Background Each year, over 15,000 preschoolers die from unintentional injuries in China. Many interventions proven to work in other nations have not been implemented nationwide in China. The rapid popularity of smartphones offers an opportunity to overcome this limitation and disseminate evidence-based interventions to the large population of China. This study aims to assess the effectiveness of an app-based intervention for caregivers of preschoolers to prevent unintentional injury among young Chinese children. Method A single-blinded, 6-month, parallel-group cluster randomized controlled trial with 1:1 allocation ratio will be conducted in Changsha, China. In total, 2626 caregivers of preschoolers ages 3-6 years old who own a smartphone will be recruited from 20 preschools. Clusters will be randomized at the preschool level and allocated to either the control group (routine education plus app-based parenting education excluding unintentional injury prevention) or the intervention group (routine education plus app-based parenting education including unintentional injury prevention). The app-based injury prevention program was developed based on the Theory of Planned Behavior, the Haddon Matrix, the Mobile Learning framework, and a needs assessment. Data collection will be conducted at baseline, 3-month, and 6-month follow-up via app-based survey plus printed questionnaire survey. The primary outcome measure is unintentional injury incidence among preschoolers in the past 3 months. Secondary outcome measures include economic losses due to unintentional injury in the past 3 months, the Incremental Cost-Effectiveness Ratios (ICERs), and parent's attitudes and behaviors concerning supervision to prevent preschooler unintentional injury in the past week. An intention-to-treat approach will be used to evaluate outcome measures. Chi-square tests will examine differences for outcome measures between groups at each time point and generalized estimation equations (GEE) will test the overall effectiveness of the app-based intervention. Missing outcome data will be imputed using the Expectation Maximization algorithm (EM). Discussion This trial will examine evidence concerning the effectiveness of an innovative app-based intervention for caregivers of Chinese preschoolers. If effective, the app-based intervention could offer an effective population-based intervention option to cost-effectively promote unintentional injury prevention in countries and regions where injury control is under-supported. Trial registration ChiCTR-IOR-17010438. Registered 15 January 2017.